Three‐in‐One Process to Enhance the Oxygen Evolution Activity of Tungstates: Phase Transformation, Ordered Mesoporous Structure, and Cations Synergistic Effect. Issue 5 (11th February 2020) - Wang, Tianlei; Liu, Meitang; Ma, Hongwen
Abstract : Engineering compositions and structures is the tactic for optimizing electrocatalytic properties in nanomaterials. High‐ordered mesoporous monometallic or bimetallic tungstates are first synthesized via a soft template method combined with pH regulation of the reaction solution. The addition of buffer solution not only changes the phase composition but also adjusts the hydrolysis and condensation rate to promote the formation of a mesoporous structure with the help of the template. Mesoporous cobalt‐doped iron tungstates deliver 320 mV at a current density of 10 mA cm −2 with a small Tafel slope of 52 mV dec −1, due to transformation of phase, the existence of a mesoporous structure, and the synergistic effect of metallic cations. Herein, it is confirmed that the simplicity and feasibility of rational structure design and purposive phase regulation provide vast opportunities and strategies for the research of novel oxygen evolution catalysts. Abstract : High‐ordered mesoporous tungstates are synthesized via a soft template method. The addition of buffer solution not only changes phase composition but also adjusts hydrolysis and condensation rate to promote the formation of mesoporous structures with the help of templates. Mesoporous CoFe tungstates exhibit an outstanding oxygen evolution activity, which manifests as the best electrochemical property of tungstates reported until now.